RICHARD RINEHART and JON IPPOLITO, Re-Collection: Art, New Media, and Social Memory - Furness, Amy Marshall (Archivaria, 2016)
Re-Collection: Art, New Media, and Social Memory. RICHARD RINEHART and JON IPPOLITO. Cambridge, MA, and London, UK: MIT Press, 2014. 297 pp. ISBN 978-0-262-02700-7.